Inducing mononuclear cells of patients with CADASIL to construct a CSVD disease model - Zhiqiang Wang; Jianjian Yin; Wa Chao; Xiaoning Zhang (European Journal of Medical Research)
Abstract Objective To produce pluripotent stem cells from peripheral blood mononuclear cells (PBMCs) of a patient with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) and culture and differentiate them into vascular organoids, producing a disease model for cerebral small vessel disease (CSVD). Methods (1) PMBCs from patients clinically diagnosed with CADASIL (NOTCH3 p.R141C) were induced to differentiate into pluripotent stem cells (iPSCs); the quality and differentiation ability of the iPSCs were determined. (2) CADASIL-derived iPSCs and control iPSCs were cultured and differentiated into vascular organoids. The differences in the morphological structure of the two differentiated groups of vascular organoids were observed, and both were identified. Results (1) No mycoplasma infections were detected in the iPSCs prepared from the PBMCs of patients with CADASIL. The short tandem repeat (STR) identification verified that the iPSCs originated from the patient, and the karyotype was normal. Flow cytometry and immunofluorescence detection revealed that the iPSCs expressed SSEA4, OCT4, and NANOG stem proteins. Tri-germ differentiation testing confirmed that the iPSCs expressed the endoderm markers SOX17 and FOXA2, the mesoderm markers Brachyury and α-SMA, and the ectoderm markers Pax6 and β-III Tubulin. (2) CADASIL-derived iPSCs and control iPSCs were induced to differentiate and produce endothelial networks and vascular networks, ultimately forming vascular organoids. Compared with control vascular organoids, CADASIL vascular organoids exhibited lower growth density, earlier blood vessel sprouting, longer and thinner vascular filaments, and smaller final vascular organoids. The vascular organoids from the two sources expressed the endothelial cell marker CD31, the vascular smooth muscle marker α-SMA, and the pericyte marker PDGFR-β. Conclusion Reprogramming technology can be used to induce PBMCs to become iPSCs, and a CSVD disease model can be successfully constructed by culturing and differentiating the iPSCs into CADASIL vascular organoids. The NOTCH3 p.R141C mutation suppresses the vascular differentiation process in CADASIL.